INVESTIGATING STUDENTS' ANXIETY IN CONDUCTING PROPOSAL SEMINAR AT ENGLISH DEPARTMENT OF UNIVERSITY MUHAMMADIYAH MAKASSAR - Sitti Annisa Jamar; Bahrun Amin; Ardiana (Indonesian Journal of Psycholinguistics, 2022)
This study aims to determine the types and effects of anxiety and then investigate the causes and strategies to reduce speed in the seminar proposal exam. The method used is qualitative research. The population of this research is the students of Muhammadiyah University of Makassar in 2021/2022. The number of samples is 15 students. The instruments used in this research are observation and  interview. This research was conducted for students in. in the English Department of Muhammadiyah Makassar University”. The qualitative approach used in this study. More specifically, this study uses a qualitative descriptive method. The data collection procedure is the distribution were the observation and interview. Researchers distributed observation were used to analyze data on the causes and strategies of dealing with students in the proposal exam. Meanwhile, from the interview system used to get more accurate data. The findings show that there are four causes of anxiety are (1) lack of confidence (2) lack of mastery of the material, (3) forgetting the material or blank, (4) lack of concentration. Furthermore, the researcher classified the strategies used by students to reduce their anxiety in the seminar proposal exam into several categories as follows: (1) Making Preparation (2) Taking Deep Breath, (3) Doing Physical Movement, (4) Peer Seeking, (5) Ignoring Audiences. and (6) Handling Paper or Script.